2011
DOI: 10.1007/s00425-011-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

High biological variability of plastids, photosynthetic pigments and pigment forms of leaf primordia in buds

Abstract: To study the formation of the photosynthetic apparatus in nature, the carotenoid and chlorophyllous pigment compositions of differently developed leaf primordia in closed and opening buds of common ash (Fraxinus excelsior L.) and horse chestnut (Aesculus hippocastanum L.) as well as in closed buds of tree of heaven (Ailanthus altissima P. Mill.) were analyzed with HPLC. The native organization of the chlorophyllous pigments was studied using 77 K fluorescence spectroscopy, and plastid ultrastructure was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Following dormancy, the bud resumes a quiescent but receptive state with a connected symplast. Studies of several woody species have shown that the internal tissues and leaf primordia of quiescent buds are largely etiolated and lack chlorophyll (Solymosi et al, 2012). The plastids in such buds, however, exist in different developmental stages that are partly related to the nature of the tissues in which they reside (Solymosi et al, 2012).…”
Section: Light Oxygen and Chloroplast Functions In Perennial Bud Bumentioning
confidence: 99%
See 4 more Smart Citations
“…Following dormancy, the bud resumes a quiescent but receptive state with a connected symplast. Studies of several woody species have shown that the internal tissues and leaf primordia of quiescent buds are largely etiolated and lack chlorophyll (Solymosi et al, 2012). The plastids in such buds, however, exist in different developmental stages that are partly related to the nature of the tissues in which they reside (Solymosi et al, 2012).…”
Section: Light Oxygen and Chloroplast Functions In Perennial Bud Bumentioning
confidence: 99%
“…Studies of several woody species have shown that the internal tissues and leaf primordia of quiescent buds are largely etiolated and lack chlorophyll (Solymosi et al, 2012). The plastids in such buds, however, exist in different developmental stages that are partly related to the nature of the tissues in which they reside (Solymosi et al, 2012). For example, proplastid-like and etio-chloroplasts, respectively, were identified in the inner and outer leaf primordia of compactly closed common ash (Fraxinus excelsior) buds (Solymosi et al, 2012).…”
Section: Light Oxygen and Chloroplast Functions In Perennial Bud Bumentioning
confidence: 99%
See 3 more Smart Citations